Synthesis of three-dimensional BCN foam by template-assisted CVD - Fong, Gregory Xie Yi (2018)
All professional athletes around the world are constantly training hard to suppress themselves, to break their own personal record, which will eventually lead to global recognition by breaking the world record set by their peers. Apart from their own individual effort, there are other factors that can affect their overall performances, which comes in the form of the equipment that they use during their personal training phase. This FYP project will solely focus on the synthesis of a better material that can be used to replace the conventional midsole material of a sports shoes, which not only boost the running performance of athletes, and at the same time retain the same level of comfort and protection that a conventional sport shoe can provide. Boron Carbon Nitride (BCN) foam were chosen as potential midsole material, due its unique mechanical properties. The chosen materials have high energy return, as well as relatively high strength to weight ratio. In addition, it also possesses high chemical and thermal stability which makes it the ideal choice material for use as foam based application. The foam material is produced using a single step chemical vapor deposition methodology, where Nickel (Ni) powder is used as the base template along with melamine diborate as the solid precursor to synthesis the BCN foam. After which the BCN foam is annealed at various temperature to obtain BN foam, as well as to remove Nickel. The X-Ray Diffraction machine (XRD) and Fourier Transform Infrared Spectroscopy machine (FTIR) is utilized to confirm the elemental composition of the BCN foam, for presence of BCN and Carbon (C). The Secondary Electron Microscope (SEM) was used to observe the BCN foam microstructure, mainly to observe the size of the pores.